The chemistry and biology of volatiles - Herrmann, Andreas (John Wiley & Sons, 2010)
The Chemistry and Biology of Volatiles takes an interdisciplinary approach to volatile molecules. Review-style introductions to the main topics in volatile chemistry and biology are provided by international experts, building into a broad overview of this fascinating field